Analisa Kemampuan Perawat dalam Mengklasifikasi Pasien Cedera Kepala Berdasarkan Nilai Glasgow Coma Scale (GCS) - Rizky Meilando (Ilmiah Institut Citra Internasional, 2020)
Head injury is the leading cause of death, mortality and morbidity figures a head injury was nearly a third cause of death in patients with multitrauma in different countries especially Indonesia. Data on Hospitals Depati Hamzah City Pangkalpinang, in 2015 the total number events head injury by as much as 200 cases in the year 2016 total number events head injury as much as 262 cases, and in 2017 the amount of the total figures for the incidence of head injury as many as 197 cases. The purpose of this research is to analyze the ability of nurses in classifying patients of head injury based on the value of the GCS in IGD Hospitals Depati Hamzah City Pangkalpinang year 2018. Type of this research is descriptive research with qualitative approach. . The collection of data through in-depth interviews. Results of the study showed that nurses in hospitals IGD Depati Hamzah has quite a good knowledge, nurses take action in accordance with SOP (Standard Operational procedures), the nurse must be at least certified training BTCLS, and not There is supervision at IGD Hospitals Depati Hamzah City Pangkalpinang.This research is need for advice of delivery of dissemination of SOP to the clerk in the IGD so that all employees in the good doctor's or nurse's IGD know about it and the need for reactivation of the existing supervision systems at home sick, and need an increase in knowledge and Human resource through the addition quota BTCLS training.